Mechanotransduction in high aspect ratio nanostructured meta-biomaterials: The role of cell adhesion, contractility, and transcriptional factors. (December 2022) - Modaresifar, Khashayar; Ganjian, Mahya; Díaz-Payno, Pedro J.; Klimopoulou, Maria; Koedam, Marijke; van der Eerden, Bram C.J.; Fratila-Apachitei, Lidy E.; Zadpoor, Amir A.
Abstract: Black Ti (bTi) surfaces comprising high aspect ratio nanopillars exhibit a rare combination of bactericidal and osteogenic properties, framing them as cell-instructive meta-biomaterials. Despite the existing data indicating that bTi surfaces induce osteogenic differentiation in cells, the mechanisms by which this response is regulated are not fully understood. Here, we hypothesized that high aspect ratio bTi nanopillars regulate cell adhesion, contractility, and nuclear translocation of transcriptional factors, thereby inducing an osteogenic response in the cells. Upon the observation of significant changes in the morphological characteristics, nuclear localization of Yes-associated protein (YAP), and Runt-related transcription factor 2 (Runx2) expression in the human bone marrow-derived mesenchymal stem cells (hMSCs), we inhibited focal adhesion kinase (FAK), Rho-associated protein kinase (ROCK), and YAP in separate experiments to elucidate their effects on the subsequent expression of Runx2. Our findings indicated that the increased expression of Runx2 in the cells residing on the bTi nanopillars compared to the flat Ti is highly dependent on the activity of FAK and ROCK. A mechanotransduction pathway is then postulated in which the FAK-dependent adhesion of cells to the extreme topography of the surface is in close relation with ROCK to increase the endogenous forces within the cells, eventually determining the cell shape and area. The nuclear translocation of YAP may also enhance in response to the changes in cell shape and area, resulting in the translation of mechanical stimuli to biochemical factors such as Runx2. Graphical abstract: Image 1